Toxicity studies of agarwood essential oil in vero cells using electrical impedance sensor - Mohd Mansor, Ahmad Fairuzabadi; Abbas, Phirdaous; Hamdan, Taufik Hakim; Hashim, Yumi Zuhanis Has-Yun; Nordin, Anis Nurashikin (UTM Press, 2017)
Natural products have traditionally been used for medicinal purposes in Asian communities. Toxicity studies typically use animal testing to predict the harmfulness of a particular substance to human health. For this study, in lieu of animal testing, we utilized cell-based biosensors to evaluate the toxicity of natural products. The cell-based biosensors were fabricated on a printed circuit board with copper electrodes and equipped with PDMS cell culture chambers. Two different electrodes (interdigitated and circular) were designed. Vero cells were used to represent normal healthy cells. The cells were first cultured on the biosensors and then inoculated with natural products, Taxol (chemo drug – positive control), and DMSO (negative control). Impedances of these biosensors were afterwards recorded at six-hour intervals for 80 hours to determine the growth of the cells. It was found that as compared to Taxol, natural products have substantially low toxicant values.